First Church on Berkeley Street at Marlborough Street, ca. 1869 - Hawes, Josiah Johnson (Tufts Archival Research Center, 2005)
Street-level view southwest of First Church from the north side of Marlborough Street. The church is located on Berkeley Street at Marlborough Street. Its facade faces northeast. Marlborough Street runs along the north wall of First Church, and houses can be seen behind or to the west of the church. Other buildings in the Back Bay area are visible in the photograph, including those lining Marlborough and Berkeley Streets, as well as others seen in the background, to the south of the church and along the left side of the photograph. Construction sites are included in both the foreground and center-left portion of the photograph. Laborers are included in the photograph. Wrought iron fencing encircles the property located at the northeast corner of Berkeley and Marlborough Streets. Copyprint; First Church constructed in 1867 and rebuilt in 1971 after a 1968 fire. Donated by Robert Severy. 7 1/8 diameter (image is round), 10 x 8 1/16 overall Photographs